Neural mechanisms underlying strain preference behaviour and plasticity in mice - Kai-zhen Peng; Li-li Tan; Shi-yu You; Jie Li; Yuan-yuan Xu; Jun-yang Chen; Meng-xue Wu; Liu-ting Qin; Xiao-min Zhang (Scientific Reports)
Abstract All social animals, including humans, have different social identities that generate unique social interactions. Social preference behaviours, including social integration, prosocial behaviour, and cooperation, have a wide impact on an individual’s social life. However, the neural mechanisms underlying social preferences are not yet clear. In this study, using mice as model animals, we investigated strain preference, which is a social preference based on social identification. We revealed, for the first time, that the social behaviour strain preference of mice is heterogeneous; that is, C57 mice prefer to interact with mice of the same strain, whereas KM mice prefer to interact with mice of a different strain. We further confirmed that strain preference in mice can be plastically altered by changing the nurturing environment and increasing social exposure to mice of other strains. Finally, we screened brain regions related to mouse strain preference and revealed that the activity of the periaqueductal grey (PAG) was not only consistent with the social preference of both C57 and KM mice but also coordinated with the alteration in social preference. We subsequently used muscarine to inhibit the PAG in C57BL/6J mice and found that the strain-specific social preference in C57 mice disappeared. These results showed that the PAG is a key brain region for regulating strain preference and its plasticity. This work fills a gap in the study of strain preferences in social preference research.